2004
DOI: 10.4049/jimmunol.173.5.3093
|View full text |Cite
|
Sign up to set email alerts
|

p21Cip1 and p27Kip1 Act in Synergy to Alter the Sensitivity of Naive T Cells to TGF-β-Mediated G1 Arrest through Modulation of IL-2 Responsiveness

Abstract: Induction of G1 arrest by TGF-β correlates with the regulation of p21Cip1 and p27Kip1, members of the Cip/Kip family of cyclin-dependent kinase inhibitors (cki). However, no definitive evidence exists that these proteins play a causal role in TGF-β1-induced growth arrest in lymphocytes. In this report we show the suppression of cell cycle progression by TGF-β is diminished in T cells from mice deficient for both p21Cip1 and p27Kip1 (double-knockout (DKO)) only when activated under conditions of optimal costimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 27 publications
(33 reference statements)
4
49
0
2
Order By: Relevance
“…Contrary to this results are the findings by Inman and Allday [33] which showed that TGF-b was associated with cleavage of PARP, a DNA repair enzyme but with no change in the levels of Bcl-2, an antiapoptotic protein. The inhibition of proliferation is at the G 1 phase of the cell cycle through p21, which are in agreement with the results obtained in this study [34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Contrary to this results are the findings by Inman and Allday [33] which showed that TGF-b was associated with cleavage of PARP, a DNA repair enzyme but with no change in the levels of Bcl-2, an antiapoptotic protein. The inhibition of proliferation is at the G 1 phase of the cell cycle through p21, which are in agreement with the results obtained in this study [34].…”
Section: Discussionsupporting
confidence: 93%
“…For TGF-b to function properly, expression of p53 is crucial. On the other hand, p21 over-expression increased sensitivity of T-cells to TGF-b [34]. Lack of proper levels of p53 involves a defective cytostatic response to TGF-b and the incapability to switch on the expression of the CDK inhibitor, p21 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest induced by TGF-b1 in the G1 phase is mediated by up regulation of cell-cycle inhibitors p21 and p27 and down regulation of CDK4 [6]. Recently it could be demonstrated that suppression of cell cycle progression by TGF-b1 is reduced in T cells from mice deficient for both p21 and p27 only when activated under conditions of optimal costimulation, however, TGF-b1 seemed to be able to maximally suppress the proliferation of these T cells when activated under conditions of low costimulatory strength [26]. Our finding suggests that the mechanism by which proliferation and entry into the cell cycle is inhibited upon exposure to TGF-b1 can be overcome with adequate stimulation via the TCR.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of p15 Ink4b by TGF-β in astrocytes is dependent on functional Smads and is dramatically altered in human glioma cell lines [137]. In transgenic mice that are deficient for both p21 Cip1 and p27 Kip1 , suppression of cell cycle progression is diminished in T-cells when activated under conditions of optimal co-stimulation [189]. TGF-β is able to maximally suppress the proliferation of T-cells from p21 Cip1 and p27 Kip1 double null transgenic mice when it is activated under conditions of low co-stimulatory strength.…”
Section: Introductionmentioning
confidence: 99%